2017
DOI: 10.4172/2469-9853.1000142
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Microbial Community Involved in Coking Wastewater Treatment System

Abstract: Biological treatment processes are the most important step for removing various nutrient matters due to their high removal efficiency and low operational cost. The activated sludge technology was used extensively in coking wastewater biological treatment processes where a complex prokaryotic microbial consortium played an important role in the processes of oxygen-depleting organics, toxics and nutrients removal and preventing discharge of pathogens. Thus, a thorough knowledge of the ecology of the coking waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Most abundant genera showed no significant difference between the two subsystems ( p > 0.05). The minor differences may be attributed to the elasticity of the biological diversity, but will not affect their function [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most abundant genera showed no significant difference between the two subsystems ( p > 0.05). The minor differences may be attributed to the elasticity of the biological diversity, but will not affect their function [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in molecular biology (e.g., the introduction of high-throughput DNA sequencing methods) aided to decipher the detailed taxonomic structure of microbial communities in the bioreactors. Studies revealed that members of the phylum Proteobacteria are the most abundant microorganisms in the bioreactors, contribution of the phyla Bacteroidetes, Acidobacteria, Firmicutes, Actinobacteria and Planctomycetes is also remarkable in most cases, and archaea represent a negligible fraction of the bioreactor communities (Jia et al 2016;Ma et al 2015a, b;Meng et al 2016;Xu et al 2016;Zhu et al 2015Zhu et al , 2017Ziembińska-Buczyńska et al 2019).…”
Section: Key Microorganisms In Bioreactorsmentioning
confidence: 99%
“…Although the removal of phenolics is usually carried out by bacteria, some fungi (Aspergillus sp., Fusarium sp., thiocyanate degradation, denitrification Banerjee (1996), Felföldi et al (2010), Katayama et al (1992), Ma et al (2015a, b), Meng et al (2016), Raper et al (2019b), Xu et al (2016), Zhu et al (2015Zhu et al ( , 2017 Penicillium sp., Graphium sp.) were also isolated from stainless steel industry wastewaters that are capable of phenol degradation (Santos and Linardi 2004) or were reported to be able to degrade phenolic compounds present in coking wastewater (Lu et al 2009).…”
Section: Phenol-degrading Bacteriamentioning
confidence: 99%
See 1 more Smart Citation